An overview of the key concepts required for managing a laboratory animal (rodent) facility (Journal of Laboratory Animal Science, 2024)
The use of laboratory animals primarily rodents (mice) has increased over the past 20 years especially withthe availability of transgenic and mutant strains. This increased use of mice along with novel research modelswith unique needs, has contributed to the evolution of the modern vivariums, decontamination equipment,imaging cores, ultra clean barriers, decontamination of feed and water etc. In addition, the industry hasalso made significant improvement in operating animal facilities. Automation of cage processing is just oneexample that signifies the sophistication which is an ongoing process. This sophistication and availability ofbetter options not only improved animal welfare and ergonomics, but also efficiency in operating the modernanimal facilities. As the animal facility operation involves several components, it could be challenging foran entry level manager to be knowledgeable about the best options that suits the needs of the facility. Thisarticle provides an overview of the most popular practices for the crucial aspects of animal care involvinghousing, animal health monitoring, feed and watering systems in addition to quality aspects. To provide acomplete review of the laboratory animal facility operations and management would exceed the scope of thisarticle. However, the topics discussed here are worthy of note when assessing the essential care and welfareof laboratory animals
Keywords: laboratory animals,; rodents, facility,; management,; feed and water quality,; health monitoring,; decontamination.